(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The present study shows an easy, quick, and reliable reverse-phase high-performance liquid chromatography method for measuring both erlotinib and ramucirumab. For the separation and quantification, an Inertsil column (150 × 4.6 mm, 3.5 μ) is used and a mobile phase comprising acetonitrile and 0.1% formic acid (50:50) combination was utilized. A UV detector was used to locate the eluents at 236 nm, and the flow rate was 1.0 mL/min. The retention times were found to be 2.936 and 4.535 minutes, respectively. The suggested approach was validated in accordance with ICH guidelines Q2 (R1), and it was found that the linearity of the findings fell between 2.50 and 15.00 μg/mL for ramucirumab and between 37.50 and 225.00 μg/mL for erlotinib. Erlotinib and ramucirumab demonstrated recovery rates of 99.6 and 100.1%, respectively. The robustness, accuracy, precision, and linearity range of the proposed method were all validated.